Biophysical Characterization of cubosomal nanoparticles intended for drug delivery applications and its interaction with a model drug: the miltefosine case - Malheiros, Barbara (2018)
Nanomedicine is one of the most promising fields in nanotechnology nowadays. The use of nanoparticles as carriers aims to improve efficiency of drugs that possess low solubility in aqueous environment (very hydrophobic molecules) or that have a lot of undesired side effects. In this way, nanoparticles offer both a protection for the molecules and a carrying vehicle. On this ground, cubosomes are nanoparticles capable of storing both hydrophilic and hydrophobic molecules within its structure, in addition, cubosomes have approximately 50% hydrophilic and hydrophobic areas. Therefore, they can carry much more molecules than liposomes for instance. In particular, cubosomes are quite easy to produce due to its base product, lipids (like monoolein (GMO) or phytantriol (PHY)) that self-assembly in water media. In this project, both lipids were chosen to produce the cubosomes from well-established protocols in literature. A model drug, miletofsine (MILT), was chosen to study the interaction of such nanosystem with a guest molecule. GMO cubosomes revealed to have Im3m crystallographic symmetry and lattice parameter 15.3(7) nm, particles presented sizes 300(8) nm and moderate polydispersion 0.160(20). TEM revealed squared particles with sizes ~350 nm, cryo-EM presented particles with internal structure and varied size (from 200 to > 500 nm). From FFT analysis, the calculated lattice parameter remained in the order of ~10 nm compatible with SAXS measurements. MILT loading into cubosomes was possible up to 4% w/w without loss of cubosomes structure. For 5% w/w MILT, the nanoparticles were already loosing their crystalline structure, as evidenced by cryo-EM. TEM analysis reveals that as more MILT is loaded into the cubosomes, their sizes increased. For sample 1.5% w/w MILT cryo-EM presents nanoparticles with organized internal structure and an envelope (hypothesized to be a polymer coating) in its surface. Calculated lattice parameters are in the order of ~10 nm. Myverol (Myv) is a commercial mixture that contains ~60% GMO, in this project it was proposed a bottom up protocol for Myv-based cubosomes. The production of these nanoparticles also revealed, by SAXS, Im3m symmetry and lattice parameter 12.30(12) nm. DLS revealed particle size 280(5) nm and moderate polydispersion 0.115(52). TEM shows square and cubic nanoparticles with sizes ~500 nm. MILT loading into Myv-cubosomes revealed that the drug interacts with the nanoparticle by enlarging their lattice parameter as more MILT is loaded (up to 4% w/w). Curiously, for some MILT concentrations the presence of other unknown cubic structures was evidenced by SAXS. TEM revealed nanoparticles with huge polydispersion, with sizes raging from 200 nm to 2 µm. PHY based cubosomes were successfully reproduced by the chosen protocol, in both water, PBS buffer and 2.25% glycerol medium. SAXS revealed crystallographic structure Pn3m and lattice parameter 6.74(04) nm. DLS measured sizes ~450 nm and moderate polydispersion 0.161(10). NTA measurements were consistent with DLS, revealing a broad size distribution and total particle concentration of ~1016 particles/mL for each sample. TEM revealed square and rounder particles in varied size. Cryo-EM micrographs presented particles with internal structure and varied size confirming moderate polydispersion. The FFT analysis revealed calculated lattice parameters ~6.5 nm, compatible with SAXS data. Samples were submitted to lyophilization and found that after re-hydration they still hold the same characteristics (morphology, size) as the original sample. Extrusion was also performed in order to improve polydispersion and control particle size, again cubosomes held their internal structure after the process, diminishing their sizes and improving monodispersion. MILT was loaded into cubosomes via co-solubilization and addition after the nanoparticles were formed. Up to 5% w/w the cubosomes incorporated MILT without loss of crystallographic structure, but at 10%, 15% and 20% w/w, the drug provoked phase change for Im3m symmetry. At the lower concentrations, MILT enlarged the lattice parameter of cubosomes and it was hypothesized that MILT inserted itself into the bilayer of the nanoparticles. DLS reveales that the drug does not change particle size or polydispersion. TEM revealed square and rounder particles in sizes slightly bigger than DLS. For sample 4% w/w, Cryo-EM presented particles with internal structure and calculated lattice parameter ~7 nm compatible with SAXS measurements for this sample. Co-solubilization and addition after nanoparticle preparation proved out to have the same effect on cubosomes loaded with MILT. All samples were submitted to higher temperatures to investigate phase change, based on phase diagram of the lipid. It was found that for the blank samples at 65 °C the cubosomes suffer phase change for isotropic phase L2, when MILT is loaded into the nanoparticles this phase change does not happen. DLS revealed also that at higher temperatures, particle size does not change, neither polydispersion. Finally, cubosomes proved to be remarkable nanoparticles that hold their physico-chemical characteristics even when submitted to extreme environments (lyophylization, extrusion and higher temperatures.)